2016
DOI: 10.1177/0093650215613137
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Engaged Workforce

Abstract: Scholars have increasingly recognized the importance of studying factors leading to employee engagement. However, few researchers have created and tested theoretical models that propose mechanisms linking employee engagement to social contextual variables. Based on a random sample of employees (n = 391) working across different industrial sectors in the United States, we proposed and tested a model (rooted in the Social Exchange Theory and the Job Demands-Resources Model) that examined how authentic leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 31 publications
6
66
0
9
Order By: Relevance
“…Every organization needs to address its employee relations as same as it approaches its relationships with other major stakeholders. Symmetrical and clear communication with employees is perceived as a positive and strong driver for employee engagement (Jiang and Men, 2015). Aligning the studies with the same, a research was conducted by taking 438 sales representative of a South Korean leading cosmetic company in order to test the hypotheses linking symmetrical communication and employee engagement positively and significantly.…”
Section: The Effect Of Communication On Employee Engagementmentioning
confidence: 99%
“…Every organization needs to address its employee relations as same as it approaches its relationships with other major stakeholders. Symmetrical and clear communication with employees is perceived as a positive and strong driver for employee engagement (Jiang and Men, 2015). Aligning the studies with the same, a research was conducted by taking 438 sales representative of a South Korean leading cosmetic company in order to test the hypotheses linking symmetrical communication and employee engagement positively and significantly.…”
Section: The Effect Of Communication On Employee Engagementmentioning
confidence: 99%
“…ISSN 2162-3058 2020 transparent internal communication Demonstrate the genuine interest of the organizational leaders to maintain and enhance the relationship with employs following that transparency is opposite of secrecy It is characterized by openness (Rawlins, 2009) Internal communication is characterized by transparent communication (Men & Stacks, 2014) and the strategic communication has gained that prominence in literature (Jiang & Luo, 2018)Transparent communication build organizational trust is identified by communication ( (Jiang & Luo, 2018;Rawlins, 2008) And help in employee-organization relationships enhancement (Men & Stacks, 2014) Whereas transparency is comprised of three elements informational participatory and accountability transparency and these three -work together but are analytically distinct‖ (Balkin, J M, 1999, p. 393) . Furthermore, (Rawlins, 2008)and (Jiang & Men, 2017) they found that There's is a direct relationship between employees trust toward organization and transparent internal communication. Therefore transparent communication cultivate trust and help in overcoming issue of uncertainty.…”
Section: Authentic Leadership and Employee Organizational Trustmentioning
confidence: 99%
“…Transparent communication by organizational leaders, according to Jiang and Men (2017) is a precursor to employee engagement, which supports productivity. From a preventative standpoint, a good manager will use communication to directly confront distortions of facts to rebalance employees' attempts to reduce inequity for themselves (Bell, 2011).…”
Section: Transparency and Communicationmentioning
confidence: 99%